Roadmap Web System for Project Management in the ISO/IEC 29110 Standard - Zapata-Sanchez, Jose D. J.; Armendariz-Rodriguez, Daniel A.; Ordonez-Gutierrez, Mario C.; Acuna-Cid, Hector A.; Torres-Hernandez, Mayra A. (2023 12th International Conference On Software Process Improvement (CIMPS), 2023)
The following article proposes the design and implementation of the "RoadMap Web System for Project Management in the ISO/IEC 29110 Standard". The system arises from the need of the Unidad Profesional Interdisciplinaria de Ingeniería Campus Zacatecas (UPIIZ) to have easy to use and highly available tool for the administrative follow-up and documentary control of projects, improving the collection of evidence for audits and ensuring compliance with the Software DeveloGPent Process of the UPIIZ.